Experimental analysis of Scheffler reflector-based solar cooking system: an application of sensible and latent heat storage materials - Patel, Romil; Patel, Vikram (Penerbit Universiti Kebangsaan Malaysia, 2024)
Solar cooker with different collector like evacuated tubes collector, parabolic trough collector, flat plate collector, and Scheffler reflector collector etc are generally used for the cooking food with SHSMs or PCMs. Present research article, Scheffler reflector with combined heat storage material (one SHSM and one PCM) for late-evening cooking has been experimentally investigated. One material is placed within the inner pot of a solar cooker, while another material is placed outer pot of the solar cooker. Six combinations are formed from various SHSMs (sand, pebbles, and iron pieces) and PCM (acetamide). During the daytime, the solar cooker absorbed and stored heat from the sun, which was transferred to the cooking pot through the heat storage units. The heat required for evening cooking (Rice) has been transferred by the thermal storage system which is kept inside an insulator box. After the experiment, it was observed that food was successfully cooked in pairs of sand-acetamide, acetamide-sand, and acetamide-pebbles and partially cooked in pairs of pebbles-acetamide, iron pieces-acetamide, and acetamide-iron pieces. The water activity test is to be conducted to check the cooking quality of food, and as per the result received from the test, the range of cooking and partially cooking is differentiated between 0.928 and 0.936 and 0.948 and 0.955, respectively. The cooked food’s temperature was determined to be between 60 and 63 oC at 20:00 h. The system’s total cost and payback duration were calculated for the economic analysis resulting in 50750 INR and 9.70 years, respectively.